Effect of blended learning on teaching large classes in Faculty of Education University of Maiduguri - Babakura , Mamman; Khashiyah , Abdulfattah; Kaumi , Umara; Ahmed , Jime; Habib , M. A.; Kaltum , Ali; Tahiru , Zanna (Kashere Journal of Education, 2023)
The aim of this study is to examine the effect of blended learning on the teaching and learning large classes in among ore-service teachers in a Nigerian University. The study adopted Ex-Post Factor design to determine the effect of blended learning on teaching a large class size among pre-service teachers at the University of Maiduguri. A purposive sampling technique was to draw a sample of 1,608 from the two separates test. The data obtained were analyzed using descriptive statistics (mean and median) and an independent sample t-test to analyzed the results. The results of the study show that there is a significant difference in the mean scores of pre-service teachers taught through blended learning and those taught with the conventional approach in large classes. Similarly, there is not much difference between the mean scores of male and female pre-service teachers taught with blended learning in a large class. The findings of the study revealed that blended learning enhances the management of large classes and improve pre-service teachers’ achievement test. Therefore, blended learning integrated pedagogy is the effective strategy to manage large classrooms. The study recommends that there is a need to deploy teachers with adequate skills of handling large classes through the application of blended learning instructional strategies. Also, lecturers should be trained to develop skills and master the arts of integrating technology into their classroom teaching and management of classrooms with large population.